A Variable Switching Frequency with Boost Power Factor Correction Converter - Mallisetti Rajesh Kumar; Duraisamy Lenine; Ch Sai Babu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
This paper presents single phase Power Factor Correction (PFC) with proposed variable switching frequency (VSF) control technique. The increasing of non linear loads such as thyristor rectifiers, switching-mode power supplies, adjustable speed drives, and generate harmonic currents causing various problems to the other equipment connected to the point of common coupling. There are several disadvantages in the existing PFC control implementation based on conventional PWM control. This system considered uses a unified  overcomes such a drawback by converting a voltage source into a fast-acting current source, which is reduce the harmonics in the line current, increases the efficiency and capacity of power system.  The capacitor and inductor with voltage and current ripple with minimum ripple values was designed to absorb sinusoidal input current and to reduce total harmonic distortion (THD) in the input current with output voltage regulation. The principal of operation, theoretical analysis, simulation results on a single phase boost converter are presented.